Steinbeck on a Boar Hunt - Piotr Baracz:::Creator::::::::::::
John Steinbeck with unidentified Polish hosts on a boar hunt. Steinbeck's quote about the boar: 'They were running so nicely I didn't have the heart to take aim.' This was in the Kraina Tysiaca Jezior region of Poland. See also photos 0-139; 0-957; 0-355; 1-344; 1-496; 1-497.